Good Corporate Governance Terhadap Nilai Perusahaan Pertambangan Sub Sektor Minyak dan Gas Bumi Tahun 2018 – 2022 - Fauziah Ayu Lestari; Shiwi Angelica Cindiyasari Sihono (Universitas Sam Ratulangi, 2024)
This research aims to determine the audit committee (KA), independent board of commissioners (DKI), management ownership (KM), and institutional ownership (KI) to evaluate their influence on company value from 2018 to 2022 in oil and gas mining companies listed on the Stock Exchange Indonesia. This research uses a quantitative research approach by utilizing secondary data sources such as annual reports from various companies. Seven companies were selected using a purposive sampling approach, which was based on certain criteria. Descriptive statistics, assumption tests in multiple linear regression, determination and hypothesis tests, partial tests, and f tests are some of the data analysis approaches used in this research. We used SPSS 24 in conducting this research. The conclusion drawn in this research is that the audit committee has a negative but significant influence on company value. Meanwhile, managerial ownership has a positive and significant influence on company value. This is different from an independent board of commissioners and institutional ownership which do not affect company value.